46.1k views
3 votes
(Algebra) HELP ME ASAP PLZ

(Algebra) HELP ME ASAP PLZ-example-1
User Anushka
by
4.9k points

1 Answer

7 votes

Answer:

no solution because the answer will be p=2

10 - [ 8p + 3 ] = 9 [ 2p - 5 ]

10 - 8p - 3 = [ 2p - 5 ]

-8p + 10 - 3 = [ 2p - 5 ]

p = 2 We need to get rid of expression parentheses.

If there is a negative sign in front of it, each term within the expression changes sign.

Otherwise, the expression remains unchanged.

In our example, the following 2 terms will change sign:

8p, 3

Explanation:

User Mohsen Saremi
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.